Разработка и применение сварных конструкций из труб - Гарф, Э.Ф.; Снисаренко, В.В. (Автоматическая сварка, 2008)
Показано, что Украина имеет многолетние традиции в области создания конструкций из труб и сохранила свой научный и производственный потенциал для развития этого направления в будущем. Development and application of welded structures made from tubes is inseparably linked to improvement of welding as technological process for material joining, and involves fulfillment of requirements for assurance of quality and strength of the welded joints. It is shown that Ukraine has many-year traditions in the field of fabrication of tubular structures, and that it has preserved its scientific and industrial potential for further development of this field.